OP0227 Oral C5a Receptor Antagonist CCX168 Phase 2 Clinical TRIAL in Anca-Associated Renal Vasculitis. (10th June 2014) - Jayne, D.R.; Bruchfeld, A.; Schaier, M.; Ciechanowski, K.; Harper, L.; Jadoul, M.; Segelmark, M.; Selga, D.; Szombati, I.; Venning, M.; Hugo, C.; Van Daele, P.L.; et al.
Abstract : Background: In ANCA vasculitis, the anaphylatoxin C5a amplifies neutrophil influx and activation through C5aR. CCX168, an oral specific C5aR antagonist, is in clinical development for ANCA-associated renal vasculitis (AARV). Objectives: A Phase 2 clinical trial was conducted to investigate the potential of CCX168 to contribute to disease remission and permit glucocorticoid reduction or avoidance in patients with active AARV receiving cyclophosphamide (CYC). Methods: This randomized, double-blind, placebo-controlled Phase 2 trial was performed in a stepwise manner. In Step 1 (N=12), CCX168+CYC+low dose prednisone (20 mg/day starting dose) was compared to standard-of-care (SOC) (CYC+high dose prednisone, 60 mg/day starting dose). In Step 2 (N=14), CCX168+CYC and no prednisone was compared to SOC. Eligible patients had GPA, MPA, or renal limited vasculitis, were PR3 or MPO-ANCA positive, and had active renal vasculitis with a GFR >30ml/min. The dose of CCX168 was 30 mg BID PO for 12 weeks and the dose of CYC was 15 mg/kg IV q2-3 wks. Results: Baseline characteristics and efficacy results at Week 12 are shown in the table. The number of steroid rescue events was not higher in the CCX168 groups compared to SOC. The incidence of renal remission was higher in the CCX168 groups compared to the SOC control group. The percent decrease from baseline in BVAS, urinary ACR and urinary MCP-1/creatinine was higher in the CCX168 groups compared to SOC. Renal function, as measured by eGFR, increased in all 3 groups, with the largest increase (6.8 mL/min/1.73 m 2 ) in the CCX168+low dose steroids group. CCX168 appeared to be well tolerated. No unexpected serious adverse reactions were observed with CCX168 use. There was one early withdrawal from study, in the control, SOC, group. Conclusions: CCX168 plus CYC appear to be at least as effective, if not more effective, as full dose steroids plus CYC in treatment of patients with an ANCA associated renal vasculitis flare. Disclosure of Interest: D. Jayne Consultant for: ChemoCentryx, Inc., A. Bruchfeld Consultant for: ChemoCentryx, Inc., M. Schaier: None declared, K. Ciechanowski: None declared, L. Harper Consultant for: ChemoCentryx, Inc., M. Jadoul: None declared, M. Segelmark Consultant for: ChemoCentryx, Inc., D. Selga: None declared, I. Szombati: None declared, M. Venning Consultant for: ChemoCentryx, Inc., C. Hugo: None declared, P. Van Daele: None declared, O. Viklicky: None declared, A. Potarca Consultant for: ChemoCentryx, Inc., T. Schall Shareholder of: ChemoCentryx, Inc., Employee of: ChemoCentryx, Inc., P. Bekker Shareholder of: ChemoCentryx, Inc., Employee of: ChemoCentryx, Inc. DOI: 10.1136/annrheumdis-2014-eular.3728